ANALISIS PEMBIAYAAN MURABAHAH DI BMT AMANAH UMMAH SUKODONO - Indah Ajeng Pratiwi Ate; Dewi Riza Lisvi Vahlevi (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
This study aims to determine and analyze murabahah financing at BMT Amanah Ummah Sukodono. Murabaha financing still dominates the composition of financing in Islamic financial institutions, including BMT. BMT assesses that the murabahah financing process has a small risk so that BMT spends more on this type of financing. The composition of murabahah financing which is still very large in BMT and the existence of muamalah rules which state that